The Duty to Pay Khums, from Pure Imperative Rule to Positive Rule of Joint Ownership - ????? ?????????, ??????; ?????, ??????; ???? ????????, ??????? (??? ? ????)
The duty to pay Khums and possession of its subject matter deserve reconsideration from the viewpoint of positive and imperative consequences. Such reconsideration depends on the nature of this rule and how it applies to property. The above said rule may be conceived in three ways:  pure imperative rule, positive rule of indebtedness and joint ownership (real joint ownership, joint ownership of property and joint ownership of a whole out of a specific aggregate of goods). The majority of Islamic jurists maintain that this rule is not of a pure imperative nature and evidently, a positive rule is applicable to the case as a result of the imperative rule. Nonetheless, the nature of this positive rule is contentious. According to the famous opinion, such positive rule is the realization of joint ownership for Khums owners and unless the property is destructed or there is excessive use or failure of due care, it does not indebt the duty-bound person. However, this opinion is in contrast with certain other elements of the rule. By extracting the elements of Khums and given the literal meaning of Quran verses and hadiths (traditions), one may conclude that although the initial rule in this field is its application to the physical property in the form of joint ownership, such ownership is instable for Khums owners and the property owner's possessory acts make him indebted and his possessory acts as to Khums subject-matter are valid and he is merely responsible for the value and price of Khums.